THE USE OF A MOBILE APPLICATION TO IMPROVE THE ORAL HEALTH OF CHILDREN WITH AUTIS - Stamatović, Aleksandra; Mitrašinović, Boban; Pavlović, Andjela; Marković, Dejan; Jovanović, Olja; Vranješević, Jelena; Jovanović, Julijana; Ostojić, Dejan; Ilić, Jugoslav; Vuković, Ana (HEALTH CARE, 2023)
Introduction: Individuals with autism spectrum disorder (ASD) often encounter significant challenges when visiting a dentist. Mobile supportive technologies have shown promise as effective assisting tools in promoting oral health-related tasks. This study aimed, in its first stage, to investigate the availability of oral health mobile applications in the Serbian language and Cyrillic script. In the second stage, our goal was to evaluate the effectiveness of an application designed specifically for dentist visits, developed in the Serbian language and using the Cyrillic alphabet.Method: The cross-sectional study was conducted from November 2021 to February 2022 at the Clinic for Pediatric and Preventive Dentistry at the School of Dental Medicine in Belgrade, Republic of Serbia. The initial stage involved conducting a search of online apps, both in Serbian and English, using specific keywords: "mobile applications," "autism," "dentistry," and "oral health." In the subsequent stage, a sample of 10 families of children with ASD utilized a mobile app in Serbian and using Cyrillic script specifically developed for their dental visits. Progress in cooperation with the dentist among users of this application was assessed using a structured observation protocol based on the TEACCH method.Results: The content analysis of mobile apps reveals that out of the total number of applications, 64 (70.3%) were deemed functional. More than half of these applications (59.4%) were designed to address developmental, learning, and speech difficulties. In terms of language, only one application aimed at supporting development, learning, and speech was available in Serbian, while three apps were in Croatian, utilizing the Latin script. However, among these mobile apps, only one application was identified for oral health, and it was in English. This indicates a clear need for the development of oral health apps in Serbian. A pilot test suggested that the tested mobile app effectively supports children with ASD in their visits to the dentist.Conclusion: The research suggests that mobile apps supporting children with ASD during dentist visits are a promising tool. Therefore, efforts should be made to develop and test these types of mobile apps in the Serbian language.
Keywords: autism, cross-sectional study, online applications for maintaining and improving oral health, dentistry, children